Optimization of Pelleting Parameters for Producing Composite Pellets Using Zeolitic Material From Fly Ash - Denise Alves Fungaro; Tharcila Bertolini (AMTS and Faculty of Engineering - Universitas Riau, 2022)
Zeolitic material in powder form was prepared from fly ash by direct activation treatment. The resulted fly ash-based zeolite was pelletizing and the effect of different inorganic (calcium hydroxide, bentonite, kaolinite) and organic (dextrin) binders with varying percentage was investigated. The zeolitic materials were analyzed by XRF, XRD, SEM, FTIR, TG-DTG and Nitrogen adsorption/desorption isotherm. Compression and impact tests have been used to study the deformation and breakage behaviour of spherical granules. The best performance was obtained by zeolite granular containing 5 wt.% bentonite and 5 wt.% kaolinite with mechanical strength and satisfactory water resistance. The synthesis of pelletized zeolite from by-products derived from coal combustion provides not only environmental and economic benefits, but also contributes to achieving the principles of sustainable development.